Sociología de la urbe - Pfeil, Elizabeth (1960)
Analysing different aspects of city life during the lapse between the last quarter of last century and our days, the author points out as a remarkable feature, the unsteadiness with which men and professions are joint, upon the basis of competence and affinity, in it, stating the necessity of satisfactorily exploring the social consequences of that unsteadiness; the author also describes the situations of anonymousness and strangeness through which every new member of a large city goes, and with the example of a family illustrates the points of view and proceedings of its members with regard to neighbourhood relationship, social circle and politic and church community. Then the author devotes to urban dwelling, to end with a chapter on urban planning recommending the sociologic approach to this type of investigations. Town must be considered, not individually, but in its functional connection with the boundary, with the region, as a component of a balanced hierarchy